Structural Investigations of N-carbamoylputrescine Amidohydrolase from Medicago truncatula: Insights into the Ultimate Step of Putrescine Biosynthesis in Plants - Sekula, Bartosz; Ruszkowski, Milosz; Malinska, Maura; Dauter, Zbigniew (Frontiers in Plant Science, 2016)
Putrescine, 1,4-diaminobutane, is an intermediate in the biosynthesis of more complexed polyamines, spermidine and spermine. Unlike other eukaryotes, plants have evolved a multistep pathway for putrescine biosynthesis that utilizes arginine. In the final reaction, N-carbamoylputrescine is hydrolyzed to putrescine by N-carbamoylputrescine amidohydrolase (CPA, EC 3.5.1.53). During the hydrolysis, consecutive nucleophilic attacks on the substrate by Cys158 and water lead to formation of putrescine and two by-products, ammonia and carbon dioxide. CPA from the model legume plant, Medicago truncatula (MtCPA), was investigated in this work. Four crystal structures were determined: the wild-type MtCPA in complex with the reaction intermediate, N-(dihydroxymethyl)putrescine as well as with cadaverine, which is a longer analogue of putrescine; and also structures of MtCPA-C158S mutant unliganded and with putrescine. MtCPA assembles into octamers, which resemble an incomplete left-handed helical twist. The active site of MtCPA is funnel-like shaped, and its entrance is walled with a contribution of the neighboring protein subunits. Deep inside the catalytic cavity, Glu48, Lys121 and Cys158 form the catalytic triad. In this studies, we have highlighted the key residues, highly conserved among the plant kingdom, responsible for the activity and selectivity of MtCPA towards N-carbamoylputrescine. Moreover, since, according to previous reports, a close MtCPA relative from Arabidopsis thaliana, along with several other nitrilase-like proteins, are subjected to allosteric regulation by substrates, we have used the structural information to indicate a putative secondary binding site. Based on the docking experiment, we postulate that this site is adjacent to the entrance to the catalytic pocket.